Implementasi Peraturan Walikota Banjarmasin Nomor 18 Tahun 2016 Tentang Pengurangan Penggunaan Kantong Plastik di Kota Banjarmasin Tahun 2019 - Junaidy Inas (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2020)
The research method used is a qualitative research method with data collection techniques of observation, interviews and documentation. The results showed that the Implementation of Regulations on reducing plastic bags had been running quite optimally according to applicable regulations. In the communication aspect, it is carried out by conducting socialization through print and electronic media as well as direct counseling to relevant stakeholders. Aspect of Resources, plastic bag diet program has been supported by Apparatus and volunteers, but the funding aspect still needs to be improved simultaneously. In the aspect of disposition, implementing apparatuses carry out procedures consistently. some deficiencies in the application of the regulation are only normative such as lack of supervision and the absence of further guidance from the city government of banjarmasin to the Retail Entrepreneurs in Banjarmasin City, as well as the absence of sanctions contained in the Banjarmasin Mayor Regulation so that both coaching and enforcement can be said to be non-existent.